2019
DOI: 10.1177/1724600818803104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD37, cystatin A, and IL-23A gene expression in association with brain metastasis: analysis of a prospective trial

Abstract: Purpose/Objectives: We aimed to assess the predictive value of a lung cancer gene panel for the development of brain metastases. Materials/Methods: Between 2011 and 2015, 102 patients with lung cancer were prospectively enrolled in a clinical trial in which a diagnostic fine-needle aspirate was obtained. Gene expression was conducted on all samples that rendered a diagnosis of non-small cell lung cancer (NSCLC). Subsequent retrospective analysis of brain metastases-related outcomes was performed by reviewing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Interestingly, the very recent observations from non-small cell lung cancer (NSCLC) have suggested low expression of CD37 as a marker of metastasis. Gene expression profiling from fine-needle aspirates from NSCLC tumors has identified CD37 as one of three genes downregulated in the course of the disease progression [ 53 ]. Recent advances in tumor immunology demonstrate that tumor-infiltrating B cells influence tumor progression through the productions of antibodies, immunosuppressive cytokines such as IL-10, as well as by interacting with other immune cells [ 45 ].…”
Section: Cd37 In B Cell Lymphoma and Leukemiamentioning
confidence: 99%
“…Interestingly, the very recent observations from non-small cell lung cancer (NSCLC) have suggested low expression of CD37 as a marker of metastasis. Gene expression profiling from fine-needle aspirates from NSCLC tumors has identified CD37 as one of three genes downregulated in the course of the disease progression [ 53 ]. Recent advances in tumor immunology demonstrate that tumor-infiltrating B cells influence tumor progression through the productions of antibodies, immunosuppressive cytokines such as IL-10, as well as by interacting with other immune cells [ 45 ].…”
Section: Cd37 In B Cell Lymphoma and Leukemiamentioning
confidence: 99%
“…Dohm et al. evaluated RNA-seq data from patients who underwent fine needle aspiration for newly diagnosed non-small cell lung cancer ( 36 ). These patients were subsequently followed over the natural history of their disease and the genomics of patients who developed brain metastases were compared to those who did not develop brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our research found that IL23A was closely related to the development and prognosis of gastric cancer. Interaction between IL23 and macrophages has a significant impact on the immunotherapy of cancer [18,19]. Blogowski showed that patients with all types of gastric neoplasms have significantly lower IL23A levels [20].…”
Section: Discussionmentioning
confidence: 99%